Diagnostic methods and devices for temporomandibular disorder: Metode dan perangkat untuk diagnostik gangguan temporomandibula - Winnie Munte; Devina Angga; Ricca Chairunnisa (Makassar Dental Journal, 2021)
Temporomandibular disorder (TMD) is the most common non-dental pain in the maxillofacial region. The diagnosis and ma-nagement of TMD, remains a challenge for clinicians to this day, despite extensive clinical research into the topic. DC/TMD Protocol emerged in 1992 as Research Diagnostic Criteria for Temporomandibular Disorder (RDC/TMD). A dual-axis system of DC/TMD protocol composed of physical diagnoses (axis I) and psychosocial profiles (axis II), to diagnose TMD based on research results that is the most widely accepted and standardized tool for assessment and classification of TMD, with sensiti-vity and specificity established for the most common diagnoses of TMD. Other diagnostic tests also can provide additional in-formation that may help verify or challenge the established clinical diagnosis. There are many different types of radiographic techniques that can be used to gain additional insight into the health and function of the TMJ. The fourth techniques are pano-noramic, cone beam computed tomography (CBCT), magnetic resonance image (MRI), and bone scintigraphy. Ultrasound images of the joints and surrounding tissues also can help to diagnose TMD. Another diagnostic tool to evaluate muscle func-tion is electromyograph. Its efficiency is directly and objectively to detect electrical potential. These diagnostic methods and de-vices are commonly used by clinicians to diagnose TMD easily with determining specific tools.